Improving the Quality of Selat Village Bamboo Sunshade Crafts through the Bamboo Preservation Process - Rini, Dwi Sukma; Aji, Irwan Mahakam Lesmono; Ningsih, Rima Vera; Latifah, Sitti; Anwar, Hairil (Unram Journal of Community Service, 2025)
Selat Village in West Lombok Regency is known as a bamboo sunshade craft center with abundant bamboo resources. However, the production of bamboo blinds is still done traditionally without the application of preservation technology, making it vulnerable to attacks by destructive organisms such as powder beetles and fungi. Lack of information on effective preservation techniques leads to low product quality and selling value. Therefore, this service activity aims to provide training and assistance to artisan groups in applying simple and environmentally friendly preservation methods. The methods used include an initial survey to understand the condition of the craftsmen, counseling with a Focus Group Discussion (FGD) approach, and the design and implementation of a bamboo preservation tool based on soaking in 5% borax solution. Socialization was conducted to 30 craftsmen from the “Karya Mandiri” group and involved the village and surrounding community. The results of the activity show that the soaking preservation method is more suitable for the needs of craftsmen than the VSD method because the bamboo raw materials used are already in the form of blades. The application of this method can increase the durability of bamboo, speed up the curing process from 1 month to 7-10 days, and increase the selling value of bamboo blinds. The follow-up plan includes periodic evaluation, further training on product finishing and packaging, and promotion through social media to expand the market. This activity contributes to improving the quality and competitiveness of bamboo sunshade products, which is expected to strengthen the economy of the Selat Village community through more effective and sustainable bamboo processing.